Analisis Healing Environment pada Rawat Inap Rumah Sakit Wates Husada Gresik - Sholikah, Ilmi Syafa'atus; Utomo, Heru Prasetiyo (Universitas Medan Area, 2025)
Hospital design plays an important role in improving the recovery of diseases suffered by patients. The healing environment architecture approach is considered capable of supporting the patient's healing process because it has a connection between the environment and the overall architectural design of the building. It is known that the physical and psychological conditions of inpatients tend to be more abnormal than outpatients. On the other hand, medical personnel who work in the inpatient room more often face patient complaints, which increases the potential for stress, heavy saturation, and has an impact on patient decline. Based on this, the researcher examined the relationship between the hospital inpatient room and the concept of healing environment at Wates Husada Gresik Hospital. The purpose of this research is expected to be able to contribute ideas that can be considered in the development of hospital health facility architecture so as to increase the efficiency of patient recovery through healing environment-based health facilities. The method used in this research is a qualitative method with a descriptive approach and review of observational results and development of analysis from literature studies. The results of this study found that the natural environment and psychological aspects are the main variables in the application of the healing environment of the Wates Husada Gresik Hospital Inpatient so that it is expected to have a positive impact on the psychology of hospitalized patients.